Focal-Plane Sensor-Processor Chips - Zarándy, Ákos (Springer New York Imprint: Springer, 2011)
Focal-Plane Sensor-Processor Chips Edited by: Ãkos Zarandy Focal-plane sensor-processor imager devices are sensor arrays and processor arrays embedded in each other on the same silicon chip. This close coupling enables ultra-fast processing even on tiny, low power devices, because the slow and energetically expensive transfer of the large amount of sensory data is eliminated. This technology also makes it possible to produce locally adaptive sensor arrays, which can (similarly to the human retina) adapt to the large dynamics of the illumination in a single scene. This book introduces a selection of the state-of-the-art focal-plane sensor-processor (FPSP) array chips, design concepts, and some applications. It provides an overview of focal plane chip technology, smart imagers and cellular wave computers, along with numerous examples of current vision chips, 3D sensor-processor arrays and their applications. Coverage includes not only the technology behind the devices, but also their near- and mid-term research trends. Describes a variety of state-of-the-art vision chips; â?¢Introduces opportunities offered by the technology through application examples such as oCompact, low power, high performance visual devices; Ultra-high speed visual decision making; oBio-inspired algorithms; Includes coverage of adaptive sensing and smart sensors; â?¢Describes 3D silicon integration into sensor-processor arrays; Discusses future trends for applying memristors in topographic process